Housing for the poor: A case study of the Johannesburg inner city - Robb, Carla (African Centre for Cities, 2019)
This research focuses on the Johannesburg inner city, which is located in the Johannesburg Metropolitan Municipality, Gauteng Province, South Africa. Johannesburg inner city has had a tumultuous history, from being the most economically powerful urban centres in Sub-Saharan Africa in the early 1900s, to falling into a state of disrepair from the 1980s, the inner city is now home to more than 300 000 households. The public sector and private sector both play a critical role in the delivery of affordable accommodation opportunities in the Johannesburg inner city, but the lack of formal supply of housing for the urban poor, specifically the “poorest of the poor” is stark. It is with this knowledge that this dissertation explores the commitment, from both public and private sector, to delivering accommodation options for the poorest of the poor in the inner city. The Johannesburg inner city has seen increased involvement from the private sector in the delivery of housing since 1994. Significantly, housing delivered by the private sector is accessible to the households in the income group referred to as the gap market. The lowest income group is left to resort to the informal sector to seek shelter. The lack of adequate housing supply for this group has given rise to illegal occupation of buildings, often run by slumlords with appalling living conditions. The public sector has many plans and strategies in place with identified mechanisms to assist in increasing the delivery of accommodation for this income group. However, there is still a massive gap in the delivery. Many plans and strategies have been put in place with the intention of addressing the housing demand in the inner city. Although many of these policies and strategies, created by the government, were intended to increase the delivery of affordable rental accommodation, what is obvious is the lack of delivery. This dissertation, therefore, intends to determine why there has been no formal provision made for the lowest income group in the Johannesburg inner city and, if there are plans or mechanisms in place to rectify this, why they have not come to fruition. The City of Johannesburg Metropolitan Municipality has been criticised for not responding to the emergency accommodation cases seriously and creating realistic strategies to deal with the poorest income group or destitute. There is a lack of a programmatic approach to meet the housing demand, which is evident from the number of bad buildings in the Johannesburg inner city. Without a realistic strategy to assist this income bracket, a domino effect of failure seems to plague housing delivery in the inner city. A lack of opportunities for this income group gives rise to bad buildings, which in turn affects the livelihood of the people in the inner city, across all sectors.